Molecular analysis of genetic variability in Fusarium species using microsatellite markers - T. PRAMEELA DEVI, N.K. SINGH; K.R. KOUNDAL, R.D. PRASAD*, T.R. SHARMA, T.K. JANA, (Indian Phytopathology, 2004)
Molecular variability among 45 isolates of Fusarium species belonging to 8 different sections was studied by using universal rice primers (URPs) designed from the rice microsatellites. Amplification products obtained from the two URPs 2R and 6R ranged between 0.3 kb to 3.5 kb and total number of loci amplified were 104 and 207, respectively. Most of the F. oxysporum and its formae speciales shared common bands of 1.0, 1.5 and 3.0 kb size. A combined dendrogram of URP markers obtained from 45 Fusarium isolates formed 5 major clusters. Assessment of molecular variability based on URPs indicated clearly that F. oxysporum is heterogeneous and most of the formae speciales have close evolutionary relationships. Other species of Fusarium viz., F. graminearum, F. pallidoroseum and F. chlamydosporum were grouped separately showing low genetic similarity with F. oxysporum. DNA banding pattern specific to the species and formae speciales of F. oxysporum and other Fusarium species obtained in the present study will be highly useful for the differentiation of Fusarium isolates at molecular level.